2016
DOI: 10.1016/j.ijid.2016.05.020
|View full text |Cite
|
Sign up to set email alerts
|

Measles immunity among pregnant women aged 15–44 years in Namibia, 2008 and 2010

Abstract: Late in a large measles outbreak, 13% of pregnant women in Namibia, and almost one in four 15-19-year-old pregnant women, remained susceptible to measles. In Namibia, immunization campaigns with measles-containing vaccine should be considered for adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 20 publications
(28 reference statements)
1
3
0
Order By: Relevance
“…Women with unknown immune status could be offered the MMR vaccine as part of routine care of CHB patients prior to pregnancy if possible; however, very few cases have been reported of measles and rubella in Denmark in recent years (European CDC EC, 2017;WHO 2020a,b,c). In line with our study, reports from Asia and the Middle East showed seroprevalence estimates of antibodies against morbillivirus and rubella virus of approximately 90% (Almuneef et al 2006;Cardemil et al 2016), which is comparable to the Danish population.…”
Section: Measles Morbillivirus and Rubella Virussupporting
confidence: 91%
“…Women with unknown immune status could be offered the MMR vaccine as part of routine care of CHB patients prior to pregnancy if possible; however, very few cases have been reported of measles and rubella in Denmark in recent years (European CDC EC, 2017;WHO 2020a,b,c). In line with our study, reports from Asia and the Middle East showed seroprevalence estimates of antibodies against morbillivirus and rubella virus of approximately 90% (Almuneef et al 2006;Cardemil et al 2016), which is comparable to the Danish population.…”
Section: Measles Morbillivirus and Rubella Virussupporting
confidence: 91%
“…Seventy-one studies fulfilled the eligibility criteria (Supplementary data 4). Twenty-eight studies reported on safety [24], [25], [29], [33], [34], [35], [36], [37], [38], [39], [40], [41], [42], [43], [44], [45], [46], [47], [48], [49], [50], [51], [52], [53], [54], [55], [56], [57], [58], [59], [60], [61] and 62 reported on immunogenicity [23], [24], [25], [29], [30], [33], [34], [35], [36], [37], [39], [40], [41], [43], [44], [45], [47], [48], [50], [51], [53], [55], [56], [57], [59], [60], [61], [62], [63], [64], [65], [66], [67], [68], [69], [70], [71], [72], [73], [74], [75], [76], [77], [78], [79], [80], [81], [82], [83], [84], [85], [86], [87], …”
Section: Resultsmentioning
confidence: 99%
“…In our study, measles seropositivity increased as the number of pregnancies increased in single analyses, but this difference was not detected in further analyzes. Women who had two pregnancies had a 1.64 times higher measles seropositivity than those who had one pregnancy ( P =0.016) ( 6 ). Measles seronegativity was unrelated to the number of births in women ( P >0.05) ( 32 ).…”
Section: Discussionmentioning
confidence: 99%